2013
DOI: 10.1136/bcr-2013-200501
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent confusional episodes associated with hypomagnesaemia due to esomeprazol

Abstract: SUMMARYIn February 2011, the Food and Drug Administration informed that prescription of proton pump inhibitor (PPI) drugs may cause low serum magnesium levels if taken for prolonged periods of time. We present an ex-smoker, 76-year-old man, with high blood pressure, diabetes mellitus and Barrett's oesophagus (treated with esomeprazole since 2003) admitted due to fluctuating aphasia. Neurovascular and neuroimaging studies were normal. Dyslipidemia and atrial arrhythmia were discovered. The patient was discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 4 publications
1
12
1
Order By: Relevance
“…The systematic search strategy identified 1928 unique articles, 1895 of which were excluded during title and abstract screening. Thirty‐three remaining full text articles were assessed for eligibility, and of these, 11 met the inclusion criteria for this systematic review . Reasons for study exclusion are documented using the PRISMA flow diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The systematic search strategy identified 1928 unique articles, 1895 of which were excluded during title and abstract screening. Thirty‐three remaining full text articles were assessed for eligibility, and of these, 11 met the inclusion criteria for this systematic review . Reasons for study exclusion are documented using the PRISMA flow diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of six total cases included in this systematic review, three were case reports and three were presented as case series . Four were cases of hypomagnesemia‐associated delirium or confusion, one was a case of hyponatremic delirium, and one was a case of delirium of unknown cause . One case demonstrated that withdrawal of trial esomeprazole therapy resulted in the resolution of symptoms and restoration of magnesium levels .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• The consequences of the malabsorption: hyponatremia [17,18], deficiency in vitamin B12 [19] and hypomagnesemia [20,21] (which could have serious consequences such as confusion [22,23])…”
Section: Discussionmentioning
confidence: 99%